Performance économique et qualité institutionnelle en Côte d’Ivoire : une application au DOLS - GNOLEBA , MARTIN ZAHORE (Revue Internationale du Chercheur, 2024)
This research proposes as a goal to evaluate the role of institutional quality on economic performance and the conduct of economic and social development in Côte d’Ivoire in order to improve the macroeconomic governance of the Ivorian state. Estimates using a methodology based on the DOLS model with WDI and ICRG data for the period 1985-2019, show that corruption and socio-economic conditions hinder the performance of the Ivorian economy, while democracy significantly improves it. Therefore, the authorities in charge of managing the development of this state should clean up macroeconomic governance. In addition, the business climate must be the subject of particular attention on the part of these authorities, with a view to improving it. It is also necessary to criminalize corruption-related offences by strengthening the legislation in force, strengthening the prerogatives of the High Authority for Good Governance. Moreover, democracy must be real, and it must involve strengthening the strength of institutions of whatever nature.